2022
DOI: 10.1002/nop2.1484
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of alcohol consumption among high school students: A cross‐sectional study

Abstract: Alcohol is a psychoactive substance that causes dependence, producing a large public health burden among young people (Stockings et al., 2016). Alcohol consumption is the main cause of death and disease all around the world. It worsens brain function and increases the risk of death, injury, physical and sexual violence and many other social deviations (El Jilali et al., 2020;Kim et al., 2022).Previous research indicates that drinking is socially acceptable on certain occasions throughout Europe. For example, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, students who engage in the alcoholic experience under the influence of their intimate friends are 16 times more vulnerable to becoming alcohol dependent than those in the other groups. In redoubling the above arguments, the findings of Posavec et al 22 and Yormirzoev and Gabrielyan 24 revealed that the prevalence of alcoholic consumptions among high school students emanated from the influence of intimate partner influences. Students in the school were mocked most of the time by their beloved friends to assimilate and not get out of their friends’ moods.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, students who engage in the alcoholic experience under the influence of their intimate friends are 16 times more vulnerable to becoming alcohol dependent than those in the other groups. In redoubling the above arguments, the findings of Posavec et al 22 and Yormirzoev and Gabrielyan 24 revealed that the prevalence of alcoholic consumptions among high school students emanated from the influence of intimate partner influences. Students in the school were mocked most of the time by their beloved friends to assimilate and not get out of their friends’ moods.…”
Section: Discussionmentioning
confidence: 98%
“…Alcoholic consumption experience under the contributor category of gender has revealed significant differences in alcohol abuse between males and females. 10,22 The evidence asserted by Atkinson et al 23 and Plata et al 8 suggests that there is a correlation between the practice of drinking alcohol and the gender composition of people. The finding revealed that males are more likely to drink alcohol than females.…”
Section: Discussionmentioning
confidence: 99%
“…In line with target 4.1 of the Sustainable Development Goals (SDG) set to be achieved by 2030, the aim is to guarantee that every child, along with adolescents, gets access to quality primary and secondary education and completes it 42. However, if left unchecked, adolescent alcohol use threatens the attainment of this SDG target, as alcohol use contributes to truancy, high attrition and increased dropout rates among school-going adolescents 43 44…”
Section: Introductionmentioning
confidence: 99%
“…More worrying about drinking among adolescents now is the involvement of students in different regions of the world. In the African region, more studies on alcohol and youngsters have focused on students, with nearly all reporting an exponential increase in the inappropriate routine use of alcohol among students [18].…”
Section: Introductionmentioning
confidence: 99%